Environmental gamma radiation and rainfall measurements in the Brazilian tropical region during October to December 2019 - Martin, Inacio Malmonge (International Journal of Advanced Science and Technology, 2020)
Between October 14 and December 6, 2019, low-energy gamma rays and rainfall were monitored every minute in Sao Jose dos Campos, São Paulo, Brazil. During this period, it was possible to observe the dynamic process that occurs between the presence of low energy gamma radiation and rainfall intensity variation (mm / min) in the region. This positive correlation of (rain / ϒ - radiation) is very noticeable in the tropical region of Brazil. Due to the presence of the disintegration of uranium 238U to radium 226Ra, reaching radon 222Rn with α particle emission and low energy gamma radiation, this correlation can be verified. Rain interferes with the presence of local exhalation of radon gas causing it to be washed out in the lower atmosphere, increasing the gamma radiation intensity measured momentarily at the site. This paper shows this process observed during the mentioned above period, during which rainy and dry climates occurred.